Audiowizualne biblioteki cyfrowe w otwartym dostępie do wiedzy – wybrane projekty edukacyjne - Szerksznis, Żaneta (Lublin: Wydawnictwo Uniwersytetu Marii Curie -Skłodowskiej, 2015, 2015)
Biblioteka cyfrowa odpowiada na potrzeby współczesnych odbiorców i użytkowników Internetu. Wybrane audialne i audiowizualne biblioteki cyfrowe powstały w projektach realizowanych w obszarze dziedzictwa kulturowego. Zdigitalizowane zbiory i materiały włączone zostały za pośrednictwem nowych mediów w procesy nauczania i uczenia się. Dla dzieci i młodzieży szkolnej na 4 poziomach edukacji powstała Ninateka - audiowizualna biblioteka kultury polskiej. Rozwija edukację muzyczna, filmową, artystyczna, medialną. Dysponuje materiałami dla nauczycieli, włącza uczniów w obieg multimedialnych źródeł, rozproszonych i sprawdzonych. Treści edukacyjne pomagają wkroczyć szerokiemu odbiorcy w świat mediów, filmu, animacji i sztuki. Widz czuje się zaproszony na spektakl, koncert, wystawę. Udostępniane otwarte materiały pozwalają wszystkim odbiorcom na twórczą reinterpretację dziedzictwa kulturowego na poziomie poznawczym. Spotkanie z dziełem oddziałuje na emocje, pozwala na przeżycie katharsis. Dobrany świadomie repertuar filmów pozwala kształtować wartości i normy u młodego widza, wykorzystując walory poznawcze, wychowawcze, estetyczne i emocjonalne dzieł. Digitalizacja zasobów muzeów reprodukcji, fotografii, tekstów i scenariusze zajęć na otwartych licencjach niesie za sobą potencjał naukowy, kulturotwórczy i edukacyjny (projekt Sztuka24h, Otwarta Zachęta). Organizowane wystawy czasowe i towarzyszące im materiały edukacyjne zyskują nowe życie i wartość w publicznej przestrzeni cyfrowej Kultury 2.0. Perspektywa badawcza socjologii sztuki i spojrzenie na kompetencje odbiorców pokazują kontekst społeczny i rolę edukacyjną audiowizualnych bibliotek cyfrowych.

Digital library responds to the needs and preferences of its user internet community in its own way and with its own user policy. Along with the growing reliance of Internet web-based applications in our daily life a number of audio and audiovisual digital libraries have been created within the framework of a number of initiatives in the domain of cultural heritage. Digitized resources and collections have been integrated through new available media into the process of teaching and learning. The Ninateka portal, which is a service provided by the National Audiovisual Institute and forms an audio and visual library of Polish culture, has been established for school pupils at the four levels of education. In its intention, it is aimed at education in music, film, the arts and media. The library provides material for teachers while including pupils in the circulation of available multimedia resources. The body of the educational content help young audience enter the world of media, film, animation and the arts. The library provides online access to recordings, interviews, documentaries, experimental films, recordings of theatre performances and media coverage documenting social life. Materials made available to the viewer provide an opportunity for a young recipient to creatively reinterpret our cultural heritage. An encounter with a piece of artistic work appeals to emotions and contributes to the conscious experience of the khatarsis that eventually leads to knowledge. The carefully picked repertoire of films, spanning various genres and drawing from educational, aesthetic and emotional values in them, makes it possible to shape values and standards in the young viewer and serves the cultural goals and aspirations of young people. Digitized material of the resources of museums, of photographs, texts and non-proprietary educational aids has an enormous research, educational, culture-shaping potential (cf. Sztuka24h project or Otwarta Zachęta). Exhibitions with their accompanying educational materials that are documented in the Ninateka acquire a completely new life and value when presented in the public virtual space of the Culture 2.0.
Audiovisual digital libraries un open access to knowledge - selected educational projects
Keywords: Ninateka; Kultura 2.0; biblioteki cyfrowe